2019
DOI: 10.3390/app9183933
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Chitosan–Alginate Polyelectrolyte Complexes Loaded with Antibacterial Thyme Oil Nanoemulsions

Abstract: Biomedical industries are attempting to utilize natural materials, as they are bio-compatible, non-toxic, and show bioactive properties, like antimicrobial activity. In this study, natural polyelectrolyte complexed chitosan/alginate films (PECs) were prepared via a casting/solvent evaporation technique, and their characteristics and drug release properties were investigated. PEC films made with two different overall polymer contents, 0.4 and 1 w/v%, were loaded with thyme oil nanoemulsion as drug carrier. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…Particles are formed by enveloping the negatively charged calcium alginate complex in the pre-gel state with chitosan, and the pre-gel state is essential to enable the ionic interactions between alginate-chitosan. [24] According to Hamedi (2019), [25] a scheme of the alginate-chitosan interaction can be seen in Figure 1.…”
Section: Particle Formation Of Pequi Oilmentioning
confidence: 99%
See 3 more Smart Citations
“…Particles are formed by enveloping the negatively charged calcium alginate complex in the pre-gel state with chitosan, and the pre-gel state is essential to enable the ionic interactions between alginate-chitosan. [24] According to Hamedi (2019), [25] a scheme of the alginate-chitosan interaction can be seen in Figure 1.…”
Section: Particle Formation Of Pequi Oilmentioning
confidence: 99%
“…The alginate and chitosan spectra are described in the literature highlighting the functional groups identified in this work. [23,25] The specific interactions formed in the Calcium (Ca)-alginatechitosan matrix pequi oil microspheres may be observed in Figure 3. The alginate carboxylic group interacts with the chitosan amine and calcium to form a polyelectrolytic complex.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
See 2 more Smart Citations
“…It has excellent biocompatibility, cell-adhesive properties, and immune-stimulatory activities. [5][6][7] Studies regarding cytocompatibility of chitosan showed that it does not have acute cytotoxic effects. 8 Thyme is an aromatic and medicinal plant with representative species of Thymus serpyllum and Thymus vulgaris.…”
Section: Introductionmentioning
confidence: 99%